Análisis de la brecha digital y el teletrabajo del sector agroalimentario en la provincia de Cotopaxi - Sacatoro Lutuala, Luis Wilmer (2022)
The goal of the project is to analyze the digital breach and telework of the agrifood sector in the Cotopaxi province, in order to recognize how important the connectivity is, technologies and structural changes that have been occurring since the beginning of the pandemic, the obvious problems of the agrifood sector in the area for its adaptation to work methods such as telework have caused an acceleration in the technological adaptation process for the companies, producers, workers and the entire labor sector. The research aims to the digital breach and teleworking, the quantitative applied method, of a descriptive type, where the primary and secundary sources are analyzed over the digital breach in the agrifood sector in the Cotopaxi province and its impact on the pandemic, the addpating of changes to the digital breach. 62 companies of the sector were polled through the Google forms tool, the results are presented as a frequential analysis of the current positive and negative situations for its sector, their social, economic, environmental, and technical impact. From the results, we could notice that 60% of the administrative areas were used to the telework mode and currently only 25% is maintained with the modality of telework or semi presential, the maturity of the connectivity and implementation of ICT is in great apogee. It is important to mention that they still have to technify the sector with tools and devices for the care of the agrifood sector. It is concluded that the agrifood sector in pandemic was one of the most benefited, but also caused concern about the security and biosecurity of the food, resources are required to reduce the digital breach, supplyment, and traceability. The labor structure of companies in the agrifood sector must be improved based on the adaptation of digitalization, this modality can be semi physical where the activities and objectives of the company alternate, is another option that can be applied.